WINKLER, Martin. Ovid on Screen. A Montage of Attractions. Cambridge: Cambridge University Press, 2020. 444 p. (Nuntius Antiquus, 2021)
Resenha do livro WINKLER, Martin. Ovid on Screen. A Montage of Attractions. Cambridge: Cambridge University Press, 2020. 444 p.